Analysis of e-learning readiness level of public and private universities in Central Java, Indonesia - Saintika, Yudha; Astiti, Sarah; Kusuma, Dwi Januarita Ardianing; Muhammad, Arif Wirawan (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
The development of information technology has reached into various fields, such as education. The emergence of e-learning is one manifestation of information and communication technology (ICT) in education. Until recently, only a few universities (6%) have implemented e-learning in Indonesia. Those that have implemented e-learning are still not optimally utilized. Some experts have also warned all organizations that will adopt e-learning to be concerned with thorough preparation to avoid overruns in costs. There is a method that consists of factors to measure the level of readiness of tertiary institutions towards the implementation of e-learning. The level of readiness is obtained through the distribution of questionnaires using 5 Likert scales. This research proposed a framework that produces four factors from the university, which covers the lecturer’s characteristics, e-learning facilities, learning environment, learning management, and four factors from the student’s side, namely, self-learning, motivation, learner’s control, student’s characteristic. The measurement results show the level of readiness for e-learning implementation in tertiary institutions in Central Java Province reaches level 3 or ready but needs a few improvements. Improvements that must be made includes (1) Designing exciting learning content through interactive multimedia; (2) Increasing the frequency of e-workshops or e-training related to technological developments, especially to e-learning; (3) encouraging students to be more active in discussions and giving opinions; (4) Developing plans related to infrastructure such as servers related to their capacities; (5) strengthening the role of IT units in serving e-learning users.